Subjective wellbeing and psychological symptoms of university students during the COVID-19 pandemic: Results of a structured telephone interview in a large sample of university students - Baetens, Imke; Vanderfaeillie, Johan; Soyez, Veerle; Vantilborgh, Tim; Van Den Meersschaut, Joyce; Schotte, Chris; Theuns, Peter (Frontiers in Psychology, 2022)
University students are at elevated risk for psychological distress, especially during the COVID-19 pandemic. The aim of this study was to warmly contact our students and investigate the psychological impact of the COVID-19 pandemic on the subjective wellbeing (SWB) and levels of psychological symptoms (such as depressive and anxious feelings) of university students in Belgium. All bachelor and master students of the Vrije Universiteit Brussels (N = 15475) were invited for a brief structured telephone interview in March 2021. In total, 7154 students were assessed by a structured interview, based on the Kessler Psychological Distress Scale (K6) and the Anamnestic Comparative Self-Assessment (ACSA). Compared to a representative sample, students considered their life during the pandemic as less satisfying compared to their life before the pandemic. Overall, all students have suffered from COVID-19 and the measures taken to contain the pandemic. Twenty percent of our sample of 7154 VUB students scored above the K6 cutoff, indicating a heightened risk for having a diagnosable mental illness severe enough to cause functional limitations and to require treatment. This study highlights the need for psychological support for all students, during the COVID-19 pandemic.